1999
DOI: 10.1128/jb.181.15.4505-4508.1999
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Additional Bacteriophages with Genomes of Segmented Double-Stranded RNA

Abstract: Eight different bacteriophages were isolated from leaves ofPisum sativum, Phaseolus vulgaris,Lycopersicon esculentum, Daucus carota sativum,Raphanus sativum, and Ocimum basilicum. All contain three segments of double-stranded RNA and have genomic-segment sizes that are similar but not identical to those of previously described bacteriophage φ6. All appear to have lipid-containing membranes. The base sequences of some of the viruses are very similar but not identical to those of φ6. Three of the viruses have li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 27 publications
(30 reference statements)
2
58
0
Order By: Relevance
“…Our study addresses this limitation and lends more power to the phage ϕ6/Pph model system, because such work can now harness affordable re-sequencing approaches to compare ancestral and derived strains of bacteria. Also, recent studies show that Cystoviruses are readily found in the terrestrial phyllosphere in temperate environments, especially in association with bacteria residing on or within common legumes such as white clover plants (Mindich et al . 1999; Silander et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our study addresses this limitation and lends more power to the phage ϕ6/Pph model system, because such work can now harness affordable re-sequencing approaches to compare ancestral and derived strains of bacteria. Also, recent studies show that Cystoviruses are readily found in the terrestrial phyllosphere in temperate environments, especially in association with bacteria residing on or within common legumes such as white clover plants (Mindich et al . 1999; Silander et al .…”
Section: Discussionmentioning
confidence: 99%
“…Viruses that suppress superinfection frequently do so by downregulating the host receptor (Marschall et al 1997;Breiner 2001;Michel et al 2005); we therefore reasoned that upregulation of the /6 receptor -the host pilus (Vidaver et al 1973;Bamford et al 1976Bamford et al , 1987Roine et al 1996)could enhance coinfection by making host cells more susceptible to infection. We also reasoned that a related bacteriophage, /12, whose receptor (LPS (Mindich et al 1999)) is constitutively expressed (Whitfield and Valvano 1993) should be incapable of enhancing coinfection. Our observation that /6, but not /12, bacteriophage attach at a higher rate in populations with a higher proportion of infected hosts is consistent with these predictions and suggests the following model of coinfection enhancement in /6.…”
Section: Discussionmentioning
confidence: 99%
“…The double-stranded RNA bacteriophages /6 (Vidaver et al 1973) and /12 (Mindich et al 1999) were used in this study. /6 and /12 use as their receptor the host pilus (Vidaver et al 1973;Bamford et al 1976Bamford et al , 1987, and lipopolysaccharide (LPS) (Mindich et al 1999), respectively. The /6 strain used in this study was reconstructed from cloned genome segments (Gottlieb et al 1992) of a wildtype /6 isolate (Vidaver et al 1973).…”
Section: Strains and Cultures Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, enveloped bacteriophages φ6 (Vidaver et al, 1973) are currently discussed as suitable surrogates due to several of their advantageous characteristics such as the non-human pathogenic nature of both φ6 and P. syringae, their bacterial host (Wei et al, 2009) which allows their handling under bio safety level 1 (equivalent to minimal containment) (Gallandat and Lantagne, 2017). In addition, φ6 is easily cultivated, can be analysed rapidly using established culture techniques such as plaque assays and iscompared to other enveloped bacteriophages of the family Cystoviridae (Mindich et al, 1999) well described and characterized in literature (Laurinavicius et al, 2004). Still, a recent study by de Carvalho et al (2017) indicates that even though φ6 shows behavioural similarities to enveloped enteric viruses of the highest public health relevance, certain limitations in regards of their persistence towards temperature and their decay rate in deionized and natural waters exist.…”
Section: The Need For Standard Protocols To Compare Available Disinfementioning
confidence: 99%